Reaktivitas Antibodi Poliklonal SSV terhadap Antigen Homolog dan Heterolog - Sri Sulandari; Y. B. Sumardiyono; M. Roechan (Jurnal Perlindungan Tanaman Indonesia, 1998)
Polyclonal antibodies for Soybean Stunt Virus (SSV) were produced in white rabbit through the following procedures: approximately 100 mg of purified virions emulsified in Complete Freund’s Adjuvant (CFA) were injected intramuscularly first. In the second and third injection 150 mg of purified virions in Incomplete Freund’s Adjuvant (IFA) per injection were injected intramuscularly. Finally, about 300 mg of purified virions were injected intravenously as a booster. The injection were done at 2 weeks interval. Antiserum was collected 5 days after the final injection. Antisera was purified by precipitation in saturated ammonium sulfate. Purified antibody was tested for the titer and reactivity of antibodies against the homologous and heterologous antigen. The studies were conducted with non-precoated I-ELISA test. This research was able to obtain about 25 ml of crude antisera for SSV, the concentration of purified polyclonal antibodies was about 9 mg/ml. the titer of polyclonal antibodies was 10.000 in I-ELISA. Without absorbtion with sap of healthy plant, the antibodies could not be use to identify the infected and healthy plant samples. In the following test, the absorbed antibody was used. Using antibodies to SSV at a dilution of 1:1000 and 1:10.000 against sap extracts sample of healthy and infected plant at a dilution of 1:10 by non-precoated I-ELISA test, indicated that the antibody could be used to identify the healthy and infected samples. By the same test, the antibody could be reacted to both homologous antigen (SSV) and heterologous antigen (CMV isolated from banana).